A Friendship That Lasted a Lifetime : The Correspondence Between Alfred Schutz and Eric Voegelin - Schutz, Alfred, 1899-1959 (Eric Voegelin Institute series in political philosophy., 2011)
Scholarly correspondence can be as insightful as scholarly work itself, as it often documents the motivating forces of its writers' intellectual ideas while illuminating their lives more clearly. The more complex the authors' scholarly works and the more troubled the eras in which they lived, the more substantial, and potentially fascinating, their correspondence. This is especially true of the letters between Alfred Schutz (1899-1959) and Eric Voegelin (1901-1985). The scholars lived in incredibly dramatic times and produced profound, complex works that continue to confound academics. The communication between these two giants of the social sciences, as they sent their thoughts to one another, was crucial to the work of both men.